Empirical modeling of ducting effects on a mobile microwave link over a sea surface - Meng, Yu Song (2014)
In this paper, signal enhancement due to the ducts over a sea surface is experimentally investigated and modeled. The investigation is carried out through the study of air-to-ground mobile microwave links over a tropical ocean with low airborne altitudes (0.37 - 1.83 km) at C band (5.7 GHz). The distance-dependence of the ducting induced enhancement (with reference to the free-space propagation) is linearly modeled, and the physical variations of the ducts are found to be Gaussian distributed. Empirical ducting coefficients and parameters for the Gaussian function are estimated and provided for the prediction of the distance-dependent signal enhancement due to the ducts in similar scenarios.